1996
DOI: 10.1093/ajcn/63.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interaction of RRR-alpha-tocopheryl acetate and fish oil on low-density-lipoprotein oxidation in postmenopausal women with and without hormone-replacement therapy

Abstract: We evaluated the effects of RRR-alpha-tocpheryl acetate (alpha-tocopheryl acetate) and hormone-replacement therapy (HRT) on the oxidative susceptibility of low-density lipoprotein (LDL) in postmenopausal women consuming a fish oil supplement. The independent effect of fish oil was also assessed. Forty-eight women, equally divided between women using and not using HRT, participated in a double-blind crossover trial. Each of the four periods lasted 5 wk and was followed by a 4-wk washout interval. During each pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 38 publications
5
50
0
Order By: Relevance
“…We found a shorter lag time and a slower propagation rate after fish oil supplement, which have also been reported by others (Suzukawa et al, 1995;Wander et al, 1996;Sørensen et al, 1998;Foulon et al, 1999). The finding of a shorter lag time and concomitant reduced propagation rate after fish oil supplement may seem paradoxical: a shortened lag time is believed to reflect enhanced LDL oxidizability, while a lower propagation rate is commonly considered an indicator of decreased oxidation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a shorter lag time and a slower propagation rate after fish oil supplement, which have also been reported by others (Suzukawa et al, 1995;Wander et al, 1996;Sørensen et al, 1998;Foulon et al, 1999). The finding of a shorter lag time and concomitant reduced propagation rate after fish oil supplement may seem paradoxical: a shortened lag time is believed to reflect enhanced LDL oxidizability, while a lower propagation rate is commonly considered an indicator of decreased oxidation.…”
Section: Discussionsupporting
confidence: 92%
“…This marked decrease in both lag time and propagation rate and the increase in LDL-MDA suggests a pronounced effect of a moderate fish oil dose on LDL susceptibility to oxidation in type 2 diabetes. Earlier studies of nondiabetic subjects also found fish oil consumption to be associated with shortened LDL lag time and lowered propagation rate (Suzukawa et al, 1995;Tsai & Lu, 1997;Sørensen et al, 1998;Wander et al, 1996;Foulon et al, 1999). As the only exception, Brude et al (1997), observed neither lag time nor propagation rate changes, possibly due to insufficient statistical power (n ¼ 10).…”
Section: Discussionmentioning
confidence: 88%
“…Fish oil supplementation also produced a 15% reduction in LDL lag phase between weeks 0 and 3. This potentially adverse effect is a measure of the increased susceptibility of LDL to oxidation because of the incorporation of highly unsaturated n-3 PUFA into the phospholipids of the LDL particles, as observed in previous studies (Wander et al, 1996;Sorensen et al, 1998;Foulon et al, 1999). One of the effects of the increased consumption of fruits and vegetables was a 9.7% reduction in caloric intake, with a significant reduction in percent energy from fat from 34.9 to 30.0%.…”
Section: Discussionmentioning
confidence: 63%
“…The vast majority of studies investigating the oxidative potential of n-3 PUFAs include short-term supplementation periods (Harats et al, 1991;Nenseter et al, 1992;Bonanome et al, 1996;Wander et al, 1996;Hansen et al, 1998;Higdon et al, 2000). Long-term effects in vivo after 9 months of intervention were studied by Eritsland et al (1995), and susceptibility to lipid peroxidation induced in vitro was evaluated after 180 days of n-3 PUFAs treatment in the study by Palozza (Palozza et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of n-3 PUFAs supplementation on lipid peroxidation is controversial (Nenseter & Drevon, 1996). Several clinical studies have reported no significant change in the lipid peroxidation following increased consumption of n-3 PUFAs (Nenseter et al, 1992;Bittolo-Bon et al, 1993;Frankel et al, 1994;Eritsland et al, 1995;Bonanome et al, 1996;Wander et al, 1996;Brude et al, 1997;Hansen et al, 1998). No enhancement of the lipid peroxidation was noted after 9 months supplementation with 4 g n-3 PUFA concentrate in the shunt occlusion trial (Eritsland et al, 1995).…”
Section: Introductionmentioning
confidence: 99%